The moderating role of gender on the effect of Instagram advertising on university students in Malaysia using AIDA model - Li, Mengyao; Mokhtar, Aida (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia (IIUM), 2021)
In this research study, we examined the effects of Instagram advertising on undergraduate students by gender at a public university in Malaysia. This study adopted a quantitative research design using the survey method on a sample of 278 undergraduate students from the faculty of a public university in Malaysia. The results indicated there were moderate effects of Instagram advertisements on students of different genders. Female respondents were found to be more affected by Instagram advertisements than males in relation to the Attention-Interest-Desire-Action (AIDA) model. It is hoped that this study could contribute to current research on Instagram advertisements influencing university students’ consumer behavior using the AIDA model. Recommendations to advertisers are made in the paper.